2021
DOI: 10.1021/acs.cgd.1c00160
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of Multicomponent Crystalline Phases of (S)-Ibuprofen and l-Proline from Powder X-ray Diffraction Data, Augmented by Complementary Experimental and Computational Techniques

Abstract: Two multicomponent crystalline phases of (S)-ibuprofen and L-proline with 1:1 stoichiometry are reported, specifically a nonsolvate phase (Ibu-Pro) and a quarter-hydrate phase (Ibu-Pro-QH). Ibu-Pro was prepared only by solid-state mechanochemical synthesis, while Ibu-Pro-QH was obtained both by solution-state crystallization and by solid-state mechanochemistry. The crystal structures of Ibu-Pro and Ibu-Pro-QH were determined directly from powder X-ray diffraction (XRD) data, with structure solution carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The Kohn–Sham methods with periodic boundary conditions (periodic DFT) provided a grounded tradeoff between the accuracy and the rate of calculations of the experimentally observed properties of multicomponent organic crystals. Multicomponent crystals of pharmaceutical use often consist of ionic/zwitterionic species, which interact with neighboring molecules by short (strong) or ionic H-bonds . B3LYP and dispersion-corrected PBE are usually used in periodic DFT computations with an all-electron Gaussian-type localized orbital basis, while PBE-D3 is usually explored with the plane-wave basis sets. , Very recently, we have shown that B3LYP and PBE-D3 with fixed cell parameters provide a reasonable description of the low-frequency Raman spectra of multicomponent crystalline forms of anthelmintic drugs .…”
Section: Methodsmentioning
confidence: 99%
“…The Kohn–Sham methods with periodic boundary conditions (periodic DFT) provided a grounded tradeoff between the accuracy and the rate of calculations of the experimentally observed properties of multicomponent organic crystals. Multicomponent crystals of pharmaceutical use often consist of ionic/zwitterionic species, which interact with neighboring molecules by short (strong) or ionic H-bonds . B3LYP and dispersion-corrected PBE are usually used in periodic DFT computations with an all-electron Gaussian-type localized orbital basis, while PBE-D3 is usually explored with the plane-wave basis sets. , Very recently, we have shown that B3LYP and PBE-D3 with fixed cell parameters provide a reasonable description of the low-frequency Raman spectra of multicomponent crystalline forms of anthelmintic drugs .…”
Section: Methodsmentioning
confidence: 99%
“…X-ray diffraction analysis is a technique to characterize the solid properties of active pharmaceutical compounds. Changes in the X-ray diffraction pattern in solids resulting from intramolecular interactions indicate the formation of new crystalline phases such as cocrystals or salts [18]. Figure 1 presents the X-ray diffraction pattern of trimethoprim, citric acid, and the multi-component crystalline phase.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the process of structure determination from powder XRD is usually complemented by periodic DFT-D calculations, which improve metric parameters of covalent bonds and non-covalent interactions as well as reconcile the proton sites with an actual crystalline environment. [73][74][75][76][77][78] The latter aspect is essential for discrimination between cocrystals and salts in multicomponent structures where the extent of proton transfer is uncertain. 68,79 In this study, the PBE-D3 geometry optimization (with fixed unit cell) was applied to enhance the accuracy of the structural models obtained via powder XRD data.…”
Section: Determination and Validation Of The Crystal Structuresmentioning
confidence: 99%